JWH-018 ω-OH, a shared hydroxy metabolite of the two synthetic cannabinoids JWH-018 and AM-2201, undergoes oxidation by alcohol dehydrogenase and aldehyde dehydrogenase enzymes in vitro forming the carboxylic acid metabolite. (30th September 2016) - Holm, Niels Bjerre; Noble, Carolina; Linnet, Kristian
Highlights: Alkyl substituted synthetic cannabinoids can be oxidized by ADH and ALDH enzymes. The pentanoic acid metabolite is not formed from JWH-018 in human liver microsomes. Oxidative defluorination is cytochrome P450-independent. Abstract: Synthetic cannabinoids are new psychoactive substances (NPS) acting as agonists at the cannabinoid receptors. The aminoalkylindole-type synthetic cannabinoid naphthalen-1-yl-(1-pentylindol-3-yl)methanone (JWH-018) was among the first to appear on the illicit drug market and its metabolism has been extensively investigated. The N -pentyl side chain is a major site of human cytochrome P450 (CYP)-mediated oxidative metabolism, and the ω -carboxylic acid metabolite appears to be a major in vivo human urinary metabolite. This metabolite is, however, not formed to any significant extent in human liver microsomal (HLM) incubations raising the possibility that the discrepancy is due to involvement of cytosolic enzymes. Here we demonstrate in incubations with human liver cytosol (HLC), that JWH-018 ω -OH, but not the JWH-018 parent compound, is a substrate for nicotinamide adenine dinucleotide (NAD + )-dependent alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH) enzymes. The sole end-product identified in HLC was the JWH-018 ω -COOH metabolite, while trapping tests with methoxyamine proved the presence of the aldehyde intermediate. ADH/ALDH and UDP-glucuronosyl-transferases (UGT) enzymes may therefore both act on the JWH-018 ω -OH substrate. Finally, we note that for [1-(5-fluoropentyl)indol-3-yl]-naphthalen-1-yl-methanone (AM-2201), the ω -fluorinated analog of JWH-018, a high amount of JWH-018 ω -OH was formed in HLM incubated without NADPH, suggesting that the oxidative defluorination is efficiently catalyzed by non-CYP enzyme(s). The pathway presented here may therefore be especially important for N -(5-fluoropentyl) substituted synthetic cannabinoids, because the oxidative defluorination can occur even if the CYP-mediated metabolism preferentially takes place on other parts of the molecule than the N -alkyl side chain. Controlled clinical studies in humans are ultimately required to demonstrate the in vivo importance of the oxidation pathway presented here.